Lysine Residue 185 of Rad1 Is a Topological but Not a Functional Counterpart of Lysine Residue 164 of PCNA - Wit, Niek; Krijger, Peter H. L.; van den Berk, Paul C. M.; Jacobs, Heinz (PloS one, 2011)
Monoubiquitylation of the homotrimeric DNA sliding clamp PCNA at lysine residue 164 (PCNA(K164)) is a highly conserved, DNA damage-inducible process that is mediated by the E2/E3 complex Rad6/Rad18. This ubiquitylation event recruits translesion synthesis (TLS) polymerases capable of replicating across damaged DNA templates. Besides PCNA, the Rad6/Rad18 complex was recently shown in yeast to ubiquitylate also 9-1-1, a heterotrimeric DNA sliding clamp composed of Rad9, Rad1, and Hus1 in a DNA damage-inducible manner. Based on the highly similar crystal structures of PCNA and 9-1-1, K185 of Rad1 (Rad1(K185)) was identified as the only topological equivalent of PCNA(K164). To investigate a potential role of posttranslational modifications of Rad1(K185) in DNA damage management, we here generated a mouse model with a conditional deletable Rad1(K185R) allele. The Rad1(K185) residue was found to be dispensable for Chk1 activation, DNA damage survival, and class switch recombination of immunoglobulin genes as well as recruitment of TLS polymerases during somatic hypermutation of immunoglobulin genes. Our data indicate that Rad1(K185) is not a functional counterpart of PCNA(K164).